PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA YOUTUBE TERHADAP KEMAMPUAN MENULIS CERITA RAKYAT SISWA KELAS V UPTD SD NEGERI 122349 PEMATANGSIANTAR - Hersiana Theresia Br Sinabariba; Nancy Angelia Purba; Theresia Monika Siahaan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the Project Based Learning model assisted by YouTube media on the ability to write folklore among fifth-grade students of UPTD SD Negeri 122349 Pematangsiantar. This research employed a quantitative approach with a pre-experimental method using a one-group pretest-posttest design. The sample consisted of 28 students selected using a saturated sampling technique. Data were collected through tests, observations, and documentation, with a writing assessment rubric validated using Aiken’s V index.The results showed that students' initial ability in writing folklore was relatively low, with an average pretest score of 55.35. After the treatment, the average posttest score increased significantly to 89.64. Hypothesis testing using a paired sample t-test revealed a significance value of 0.000 < 0.05, indicating a significant effect of the Project Based Learning model assisted by YouTube media on students' writing ability.Thus, the use of Project Based Learning assisted by YouTube media is effective in improving students' ability to write folklore, while also making the learning process more engaging, interactive, and easier to understand. Keywords: Project Based Learning, YouTube, writing ability, folklore